Female cooperative labour networks in hunter–gatherers and horticulturalists. (16th January 2023) - Kraft, Thomas S.; Cummings, Daniel K.; Venkataraman, Vivek V.; Alami, Sarah; Beheim, Bret; Hooper, Paul; Seabright, Ed; Trumble, Benjamin C.; Stieglitz, Jonathan; Kaplan, Hillard; Endicott, Karen L.; Endicott, Kirk M.; et al.
Abstract : Cooperation in food acquisition is a hallmark of the human species. Given that costs and benefits of cooperation vary among production regimes and work activities, the transition from hunting-and-gathering to agriculture is likely to have reshaped the structure of cooperative subsistence networks. Hunter–gatherers often forage in groups and are generally more interdependent and experience higher short-term food acquisition risk than horticulturalists, suggesting that cooperative labour should be more widespread and frequent for hunter–gatherers. Here we compare female cooperative labour networks of Batek hunter–gatherers of Peninsular Malaysia and Tsimane forager–horticulturalists of Bolivia. We find that Batek foraging results in high daily variation in labour partnerships, facilitating frequent cooperation in diffuse networks comprised of kin and non-kin. By contrast, Tsimane horticulture involves more restricted giving and receiving of labour, confined mostly to spouses and primary or distant kin. Tsimane women also interact with few individuals in the context of hunting/fishing activities and forage mainly with spouses and primary kin. These differences give rise to camp- or village-level networks that are more modular (have more substructure when partitioned) among Tsimane horticulturalists. Our findings suggest that subsistence activities shape the formation and extent of female social networks, particularly with respect to connections with other women and non-kin. We discuss the implications of restricted female labour networks in the context of gender relations, power dynamics and the adoption of farming in humans. This article is part of the theme issue 'Cooperation among women: evolutionary and cross-cultural perspectives'.